2021
DOI: 10.18240/ijo.2021.09.05
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric ocular trauma with pars plana vitrectomy in Southwest of China: clinical characteristics and outcomes

Abstract: AIM: To investigate the clinical characteristics and predictive factors of pediatric ocular trauma patients with vitrectomy. METHODS: Pediatric ocular trauma patients (aged 14y or younger) who received vitrectomy in Southwest Hospital between January 2007 and December 2017 were reviewed retrospectively. Age, gender, mechanism of injury, final visual acuity (VA), and prognostic factors were analyzed. RESULTS: A total of 139 eyes in 139 pediatric patients were included in the study. The mean age was 7.4±3.7 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In this study, baseline BCVA was the best predictor of the final BCVA, which is consistent with previous studies. 9,11,12 Higher final BCVA was also seen, as in previous studies, [9][10][11] in the absence of PVR and older age. Prospective studies with defined success criteria are needed to assess potential outcome improvements.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In this study, baseline BCVA was the best predictor of the final BCVA, which is consistent with previous studies. 9,11,12 Higher final BCVA was also seen, as in previous studies, [9][10][11] in the absence of PVR and older age. Prospective studies with defined success criteria are needed to assess potential outcome improvements.…”
Section: Discussionsupporting
confidence: 85%
“…Despite being rare, traumatic RD resulting from open (OGI) or closed globe injuries (CGIs) is a challenging condition for retinal surgeons to address, in many cases carrying an unfavorable visual prognosis. [1][2][3][4][5][6][7][8][9][10][11][12] Open globe injury involves a full-thickness injury of the eye, often caused by sharp objects or high-velocity projectiles, leading to retinal tears or breaks. 10,[13][14][15][16][17] By contrast, CGI, often caused by a blunt impact such as sports-related injuries, falls, or physical assault, can also induce traumatic RD through indirect mechanical forces and vitreoretinal traction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the complexity and diversity of ocular trauma and the great difference in posttreatment recovery, clinicians and forensic doctors often pay great attention to the recovery of post-traumatic visual acuity (VA). To better understand visual recovery after surgery or trauma, many researchers have investigated the relationship between macular [3][4] , retinal [5][6] , and vireteal [7] injuries caused by diseases or trauma. Hou et al [8] found that macular injury involving the fovea or a thin optic nerve fiber layer results in severe vision loss.…”
Section: Introductionmentioning
confidence: 99%